Advanced asymmetric supercapacitors based on CNT@Ni(OH)2 core–shell composites and 3D graphene networks. Issue 38 (2nd September 2015) - Yi, Huan; Wang, Huanwen; Jing, Yuting; Peng, Tianquan; Wang, Yiran; Guo, Jiang; He, Qingliang; Guo, Zhanhu; Wang, Xuefeng
Abstract : Asymmetric supercapacitors with CNT@nickel hydroxide nanosheet composites and 3-D graphene networks demonstrated a high energy density (∼44.0 W h kg −1 ) and high power density (∼16 kW kg −1 ) in aqueous KOH electrolyte. Abstract : Asymmetric supercapacitors (ASCs) with carbon nanotube@nickel hydroxide nanosheet (CNT@Ni(OH)2 ) core–shell composites as positive electrodes and three-dimensional (3D) graphene networks (3DGNs) as negative electrodes were reported in aqueous KOH electrolyte. The CNT@Ni(OH)2 core–shell composites were prepared through a facile chemical bath deposition method, while 3DGNs were obtained by freeze-drying of graphene hydrogels. By virtue of their unique microstructures, superb electrochemical properties were achieved in a three-electrode system, e.g., 1136 F g −1 at 2 A g −1 for the CNT@Ni(OH)2 electrode within 0–0.5 V and 203 F g −1 at 1 A g −1 for the 3DGN electrode within −1–0 V. Benefiting from these merits, the as-fabricated CNT@Ni(OH)2 //3DGN ASC showed a maximum energy density of 44.0 W h kg −1 at a power density of 800 W kg −1 and even retained 19.6 W h kg −1 at 16 000 W kg −1 in the voltage region of 0–1.6 V.